La charte française de l'environnement: quelle efficacité ? - Dominique Bourg (VertigO)
After having briefly situated the French Constitutionnal Environment Charter in the international law context, I will introduce the institutional process we used to elaborate this text and the connexions it has with the general theme of future generations. Then, I will quickly analyse 3 articles of this Charter and show some of the reasons that allow us to expect a limited efficiency.